2008
DOI: 10.1007/s00280-008-0857-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue distribution of Kendine 91, a novel histone deacetylase inhibitor, in mice

Abstract: This preliminary pharmacokinetic evaluation prompts us to believe that it is worth pursuing further development of Kendine 91 as an anticancer drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Another HDAC inhibitor, kenedine 91, has extensive distribution that was attributed to its high lipid solubility. 30 High distribution of vorinostat to the liver as has been reported in other studies, 13 which may also account for the extensive distribution of the drug.…”
Section: Resultsmentioning
confidence: 67%
“…Another HDAC inhibitor, kenedine 91, has extensive distribution that was attributed to its high lipid solubility. 30 High distribution of vorinostat to the liver as has been reported in other studies, 13 which may also account for the extensive distribution of the drug.…”
Section: Resultsmentioning
confidence: 67%
“…They fulfill the bioavailability requirements for pharmacologically promising compounds and exhibit improved pharmacokinetics and pharmacodynamics properties compared with other HDACi. 16,25 Indeed, ex vivo assays of CLL cells demonstrated that both inhibitors reduced the viability of CLL cells, with slightly higher efficacy of Kendine 92. 16 These results lead us to consider that it is worth pursuing further analysis of Kendines as anticancer drugs.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…No significant adverse reaction was observed in all the rats, which indicated HS270 was well tolerated and safe within the dosage scope of 25-200 mg/kg. Like Kendine 91 [14], a second maximum peak was observed in the plasma profile, which could be due to enterohepatic circulation. The mean oral pharmacokinetic parameters for HS270, SAHA [15] and SB639 [15] in rats are summarized in Table 6.…”
Section: Parametersmentioning
confidence: 90%
“…A solid phase extraction system was used to extract SAHA from human plasma in previous report [11]. A liquid-liquid extraction (LLE) procedure with ethyl acetate, acetonitrile/n-butyl-chloride, and methyl tert-butyl ether has been used to extract other HDACi such as MS275, and Kendine 91 from human plasma in previous reports [6,[12][13][14]. In the present study, analytes were extracted using a single step liquid-liquid extraction.…”
Section: Methods Developmentmentioning
confidence: 99%